Fostering Patriotism: Implementing National Character Strengthening in Distance Learning at MAN 13 Jakarta - Suryani, Evi (International Journal of Contemporary Studies in Education, 2025)
This study aims to explore the implementation of patriotic character education in distance learning at Madrasah Aliyah Negeri (MAN) 13 Jakarta. In the current era of globalization, the influx of foreign cultures through various media platforms has raised concerns about the erosion of national identity among Indonesian youth. Patriotic character, defined as a deep love and respect for the homeland, is considered crucial to instill in young generations to strengthen their national identity and resilience. This research investigates how MAN 13 Jakarta integrates patriotic values into its remote learning curriculum, focusing on strategies such as singing national and regional songs at the beginning and end of classes, as well as discussing traditional Indonesian cuisines to foster a sense of pride and belonging. Through qualitative methods, including observations and interviews, this study highlights the importance of embedding patriotic character education in distance learning to cultivate conscious awareness of national values. The findings suggest that such practices not only enhance students' love for their country but also serve as a foundation for developing other essential national character traits. This research contributes to the broader discourse on character education in the digital age, offering insights into effective strategies for nurturing patriotism in a virtual learning environment.